Translation, cultural adaptation and validation of the Kidney Disease Knowledge Survey (KiKS) to Spanish - Mota Anaya,Evelin (2016)
Introduction—Chronic kidney disease (CKD) affects 50 million people globally. Several studies show the importance of implementing interventions that enhance patients' knowledge about their disease. In 2011, the Kidney Disease Knowledge Survey (KiKS) was developed, a questionnaire that assesses the specific knowledge about CKD in pre-dialysis patients. Objective—To translate to Spanish, culturally adapt and validate the questionnaire KiKS in a population of patients with pre-dialysis CKD. Methods—The translation and cultural adaptation of KiKS was performed. Subsequently, its validity and reliability were determined. The validity was evaluated by construct validity; and the reliability by its internal consistency and its intra-observer reliability (test-retest). Results—A good internal consistency was found (Kuder-Richardson = 0.85). Regarding intraobserver reliability, the intraclass correlation coefficient with a value of 0.78 (95% CI: 0.5–1.0) indicated a good reproducibility; the mean difference of −1.1 test-retest S.D. 6.0 (p = 0.369) confirm this.